2022
DOI: 10.3390/ijms23042311
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and Viral Co-Infection in the Intestine: Competition Scenario and Their Effect on Host Immunity

Abstract: Bacteria and viruses are both important pathogens causing intestinal infections, and studies on their pathogenic mechanisms tend to focus on one pathogen alone. However, bacterial and viral co-infections occur frequently in clinical settings, and infection by one pathogen can affect the severity of infection by another pathogen, either directly or indirectly. The presence of synergistic or antagonistic effects of two pathogens in co-infection can affect disease progression to varying degrees. The triad of bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 139 publications
1
8
0
Order By: Relevance
“…The Die score of S. enteritidis was dramatically reduced from 1.16 to 0.32 ( Supplementary Information Figure S2B ) thereby, favoring its overall endurance in the niche. The BW results appear to be in line with recent evidence supporting the notion that bacterial co-infection in the intestine appears to affect host immunity ( 11 ).…”
Section: Resultssupporting
confidence: 89%
“…The Die score of S. enteritidis was dramatically reduced from 1.16 to 0.32 ( Supplementary Information Figure S2B ) thereby, favoring its overall endurance in the niche. The BW results appear to be in line with recent evidence supporting the notion that bacterial co-infection in the intestine appears to affect host immunity ( 11 ).…”
Section: Resultssupporting
confidence: 89%
“…Intestinal inflammation and infection are accompanied by an imbalance in the gut microbiota [ 33 ]. Viral infections elicit an inflammatory response, resulting in gut barrier dysfunction [ 35 ]. However, the mechanism through which a dsRNA virus infection affects the gut microbiome remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…1). Studies of the virome [8,9] have revealed that virus-bacteria interactions occur in the epithelial surfaces of the oral cavity, skin, genital tract, gastrointestinal tract, and respiratory tract, and many interaction studies have concentrated on enteric viruses and intestinal bacteria [10][11][12]. Moreover, synergistic interactions between respiratory viral infections and bacterial infections also exist [13].…”
Section: Viral-bacterial Interactions Increase the Susceptibility To ...mentioning
confidence: 99%
“…The study of bacterial and viral co‐infection started with the ‘Spanish flu’ [10], as bacterial co‐infection with common upper respiratory bacteria, containing Streptococcus pneumoniae , Haemophilus influenzae , and Staphylococcus aureus , was an indispensable cause of almost all influenza deaths during the 1918 pandemic and the 2009 H1N1 influenza pandemic [15]. Bacterial co‐infection is also increasing in frequency, including in patients admitted to an intensive care unit for COVID‐19 [16].…”
Section: The Commensalism Of Microbesmentioning
confidence: 99%